The C1q Family of Proteins: Insights into the Emerging Non-Traditional Functions - Ghebrehiwet, Berhane; Hosszu, Kinga; Valentino, Alisa; Peerschke, Ellinor I. (Frontiers in Immunology, 2012)
Research conducted over the past 20 years have helped us unravel not only the hidden structural and functional subtleties of human C1q, but also has catapulted the molecule from a mere recognition unit of the classical pathway to a well-recognized molecular sensor of damage modified self or non-self antigens. Thus, C1q is involved in a rapidly expanding list of pathological disorders—including autoimmunity, trophoblast migration, preeclampsia and cancer. The results of two recent reports are provided to underscore the critical role C1q plays in health and disease. First is the observation by Singh and colleagues showing that pregnant C1q-/- mice recapitulate the key features of human preeclampsia that correlate with increased fetal death. Treatment of the C1q-/- mice with pravastatin restored trophoblast invasiveness, placental blood flow, and angiogenic balance and, thus, prevented the onset of preeclampsia. Second is the report by Hong et al., which showed that C1q can induce apoptosis of prostate cancer cells by activating the tumor suppressor molecule WW-domain containing oxydoreductase (WWOX or WOX1) and destabilizing cell adhesion. Downregulation of C1q on the other hand enhanced prostate hyperplasia and cancer formation due to failure of WOX1 activation. Recent evidence also shows that C1q belongs to a family of structurally and functionally related TNFα-like family of proteins that may have arisen from a common ancestral gene. Therefore C1q not only shares the diverse functions with the TNF family of proteins, but also explains why C1q has retained some of its ancestral “cytokine-like” activities. This review is intended to highlight some of the structural and functional aspects of C1q by underscoring the growing list of its non-traditional functions.